Upaya Meningkatkan Perhatian Belajar Ipa Menggunakan Mind Mapping Di Kelas Iv A Sd Muhammadiyah 14 Danukusuman Surakarta - NUR JUWARIYAH, LUTFI (2016)
Lutfi Nur Juwariyah / A510120113. Efforts To Improve Attention On Natural Sciences Learning Using Mind Mapping In Class IV A SD Muhammadiyah 14 Danukusuman Surakarta Year 2015/2016. Essay. The Faculty of Education, University of Muhammadiyah Surakarta. February, 2016. This study aims to determine whether mind mapping can improve students' attention and learning outcomes in science in grade IVA SD Muhammadiyah 14 Danukusuman Surakarta. The subjects of this research are the teachers of IV A and 20 students of IV A of SD Muhammadiyah 14 Danukusuman Surakarta. This research is a classroom action research. The research was conducted during two cycles or four meetings. The data were collected using interviews, observation, testing and documentation. As for the validity of the data used triangulation of sources and data collection techniques. The results showed an increase in the students' attention, namely: 1) the pre-stage cycle of 30%, 2) At the first cycle to 35%, 3) in the second cycle to 75%. As for improvement of student learning outcomes, namely: 1) the pre-stage cycle of 10%, 2) at the first cycle by 35%, 3) at the second cycle increased to 75%. The conclusion of this research is that mind mapping can improve students' attention and science learning outcomes in grade IV A SD Muhammadiyah 14 Danukusuman Surakarta in 2015/2016.